Tantangan-Tantangan dalam Memelihara Iman dalam Dunia Modern - Romlah; Burhanudin; Sumarta (Khulasah : Islamic Studies Journal, 2021)
Abstract In the modern world, characterized by technological advancements, social changes, and complexity, maintaining faith in religion has become an increasingly significant challenge. This article discusses various challenges faced by individuals in preserving their faith in the modern world. Some key challenges include the rising secularization, substantial influence of social media, religious pluralism, and increasingly complex ethical questions. Amidst ever-changing social dynamics, individuals are often confronted with pressures to adapt or even doubt their beliefs. However, this article also underscores the importance of religious education, interfaith dialogue, and religious communities in aiding individuals to confront these challenges and maintain their faith in an ever-evolving modern world. Keywords: challenges, faith, ethics and religious education